Dissemination of the Agroecological Model of Alang-Alang Land Reclamation to Increase Land Productivity - Latuamury, Bokiraiya; Putuhena, Jusmy D; Sahupala, Billy B (Jurnal Abdimas, 2023)
Using reed land for agriculture and improving productivity is cheaper than clearing forests because clearing new forests negatively impacts environmental quality. Reed control technology combined with an agroecology approach is expected to ensure a sustainable eradication of reed populations followed by technical culture and food crop cultivation patterns throughout the year. This community service program can solve food production problems, land fertility, and other environmental impacts. Community service program solutions can classify reed land based on land quality, educate the community in utilizing reed land reclamation techniques in ready-to-plant land blocks, evaluate the skills of farmers/communities based on crop production in reed reclamation blocks, and involve the community in naming superior and environmentally friendly agricultural varieties in the la block program solutions can classify reed land based on land quality, and educate the community in utilizing reed land reclamation techniques in ready-to-plant land blocks, evaluate farmer/community skills based on crop production in reed reclamation blocks, and involve the community in naming superior and environmentally friendly agricultural varieties in reed reclamation blocks.